Evaluation of Supplemental Fat Sources and Pre-Farrow Essential Fatty Acid Intake on Lactating Sow Performance and Essential Fatty Acid Composition of Colostrum, Milk, and Adipose Tissue - Julia P. Holen; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Joel M DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 91 sows (Line 241, DNA Genetics) were used to evaluate the effects of supplemental fat sources and essential fatty acid intake on lactating sow farrowing performance, litter growth performance, and essential fatty acid composition of colostrum, milk, and adipose tissue. At approximately d 107 of gestation, sows were blocked by body weight and parity, then allotted to 1 of 5 experimental treatments as part of a 2 × 2 + 1 factorial arrangement. Experimental diets were corn-soybean meal-based with a control diet that contained no added fat, or diets with 3% added fat as either beef tallow or 3% soybean oil, with consumption of the added fat diets starting on d 107 or 112 of gestation. Thus, sows were provided low essential fatty acids (EFA; as linoleic and α-linolenic acid) in diets without supplemental fat, or with beef tallow or high EFA in the diet with soybean oil. Sows were provided approximately 6 lb/d of their assigned lactation diet pre-farrow. After farrowing, sows were providedad libitumaccess to their assigned dietary treatment. Although sows consuming diets with beef tallow had greater lactation ADFI, daily linoleic acid (LA) and α-linolenic acid (ALA) intake was lower than for sows that consumed diets with soybean oil (fat source,P<0.001). Supplemental fat sources providing either low or high EFAs did not influence litter growth performance (fat source,P>0.05). Pre-farrow consumption of EFA for sows provided by beef tallow did not influence LA composition of colostrum. However, lactation diets with high EFA provided by soybean oil on d 107 of gestation increased colostrum LA composition compared to providing diets on d 112 of gestation (fat source × time, P = 0.084; time,P<0.001). Additionally, regardless of pre-farrow timing, ALA composition of colostrum increased when sows consumed diets with soybean oil compared to beef tallow (fat source,P<0.001). Both LA and ALA composition of milk at weaning was greater for sows that consumed diets with soybean oil compared to beef tallow (fat source,P<0.001). Furthermore, concentrations of LA and ALA within adipose tissue were higher at weaning when sows consumed diets with high EFA compared to low EFA (fat source,P<0.05). These responses suggest that providing dietary fat sources with high concentrations of EFAs can increase colostrum LA and ALA concentrations that can be maintained throughout lactation. However, in this experiment, changes in colostrum and milk composition did not alter litter growth performance.
Keywords: colostrum; essential fatty acids; lactation; milk composition; sow